PERAN PERILAKU KEPEMIMPINAN BERORINTASI HUBUNGAN DAN PENGELOLAAN SDM TERHADAP ETOS KERJA MELALUI RETENSI PEGAWAI DI DINAS PERHUBUNGAN KABUPATEN SUKOHARJO - Sukmajati, Amru; Marjono, Marjono (ITB AAS Indonesia Surakarta, 2024)
This study aims to find out empirically and analyze the influence of relationship-oriented leadership behavior and HR management on work ethic through Employee Retention at the Department of Transportation, Sukoharjo Regency. The population in this study were 75 employees at the Department of Transportation in Sukoharjo Regency. The sample method was a census with a sample size of 75 respondents. The analysis technique used is to use the path analysis test, t test, F test, test the coefficient of determination and correlation analysis. The results of the hypothesis test show that relationship-oriented leadership behavior has a positive and significant effect on retention. HR management has a positive and significant effect on retention. Relationship-oriented leadership behavior has a negative and insignificant effect on work ethic. HR management has a positive and significant effect on work ethics. Retention has a positive and significant effect on work ethic. The results of the F test together with relationship-oriented leadership behavior variables, HR management and retention have a significant effect on work ethic. The results of the calculation of the total R2 value of 0.815 can be interpreted as variations in the work ethic of employees at the Sukoharjo Regency Transportation Service explained by the relationship-oriented leadership behavior variables, HR management and retention of 81.5% and the remaining 18.5% explained by other variables outside the research model as examples of abilities work and communication. Conclusion Direct and Indirect Influence illustrates that the direct path of HR management on work ethic is the dominant or effective path to improve work ethic.